A Generalized Active Voltage Balancing Circuit Implementation for Flying Capacitor 3-Level Switching-Mode DC–DC Converters - Elisabetta Moisello; Samuele Fusetto; Piero Malcovati; Edoardo Bonizzoni (IEEE Open Journal of Circuits and Systems)
This paper presents a generalized control architecture for implementing the active balancing of the flying capacitor voltage in any kind of 3-level switching-mode DC-DC converters, independently from the desired conversion ratio or targeted output power level. The proposed strategy is based on the detection of the flying capacitor voltage through the inductor voltage, sensed at the switching node, and acts on the duty cycle of the PWM (Pulse Width Modulation) control signals in order to make the correction, implementing the voltage balancing. The circuit implementation and its operation are described in detail. Extensive simulations were performed in the SIMPLIS environment, taking as examples the cases of a 3-level buck, 3-level boost and 3-level inverting buck-boost DC-DC converter and considering different combinations of input voltage, output voltage and load current. Moreover, the proposed strategy was implemented in the control architecture of a hybrid switched-capacitor 3-level inverting buck-boost converter, fabricated in a 180-nm BCD process. The effectiveness and the versatility of the proposed active voltage balancing strategy and its circuit implementation were, therefore, verified both through simulations and experimentally.